ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT KONSUMEN BELANJA PRODUK HALAL SECARA ONLINE - Kiki Badrul Hikmah; Ujang Buchori Muslim; Hasbi Ash Shiddieqy (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
The development of internet technology is increasingly advanced, making this technology one of the media not only for communicating, but also for buying and selling. The unique characteristics of the internet and its worldwide reach, make e-commerce grow more rapidly. When compared to ordinary commerce, the nature of the internet can be said to be unique because it has managed to penetrate world boundaries, cut distribution chains, and is available 24 hours a day. This study aims to determine: (1) the effect of price on buying interest, (2) the effect of ease of use on buying interest, (3) the effect of trust on buying interest, (4) the effect of price, ease of use and trust on buying interest. This type of research is survey research. The population in this study were students of the Sahid Islamic Institute. The sampling method is simple random sampling with a sample of 100 people. Data were collected by using a questionnaire that had been tested for validity and reliability. The data analysis technique used is multiple regression analysis.